2005
DOI: 10.1002/pola.20523
|View full text |Cite
|
Sign up to set email alerts
|

Temperature‐sensitive hydrogel microspheres formed by liquid–liquid phase transitions of aqueous solutions of poly(N,N‐dimethylacrylamide‐co‐allyl methacrylate)

Abstract: Poly(N,N‐dimethylacrylamide‐co‐allyl methacrylate) (DMA‐co‐AMA) copolymers were prepared by the copolymerization of N,N‐dimethylacrylamide with allyl methacrylate (AMA). The methacryloyl group of AMA reacted preferentially, and this resulted in pendant allyl groups along the copolymer chains. Aqueous solutions of these DMA‐co‐AMA copolymers were thermoresponsive and showed liquid–liquid phase transitions at temperatures that depended on the AMA content. Hydrogel microspheres were prepared from these thermally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…The pendant allyl groups were used to crosslink the polymers by free radical polymerization. Microparticles were produced with diameters ranging from 14–72 µm [183]. In another study, a comb copolymer of PEG, styrene and maleic anhydride was incubated with poly(diallyldimethylammonium chloride) to form complex coacervates (carboxylic acids were present in the copolymer due to partial hydrolysis of the anhydride groups).…”
Section: Instructive Examples Of Liquid-liquid Two Phase Systemsmentioning
confidence: 99%
“…The pendant allyl groups were used to crosslink the polymers by free radical polymerization. Microparticles were produced with diameters ranging from 14–72 µm [183]. In another study, a comb copolymer of PEG, styrene and maleic anhydride was incubated with poly(diallyldimethylammonium chloride) to form complex coacervates (carboxylic acids were present in the copolymer due to partial hydrolysis of the anhydride groups).…”
Section: Instructive Examples Of Liquid-liquid Two Phase Systemsmentioning
confidence: 99%
“…In addition, in the last few years, the synthesis of polymers having polymerizable groups has been an active field of research because it provides an approach to subsequent modification of the polymers for a required application. Thus, for example, random copolymers of N,N ‐dimethylacrylamide and AMA form novel thermosensitive hydrogel microspheres, and such materials may find applications in protein separation and protein delivery 15…”
Section: Introductionmentioning
confidence: 99%
“…Studies on DMA based copolymers have reported excellent characteristics. However, the mechanical strength of these synthesized hydrogels is weak [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%